Global Financial Crises: Shaping Trends in Bank Mergers - Sali, Venkatesh; Bharadi, H H (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Global financial crises have a transformative impact on the banking sector, often necessitating structural changes to restore stability and confidence. Among these, bank mergers serve as a strategic response to address financial instability, protect depositors, and sustain economic activity. This paper investigates the historical and contemporary trends in bank mergers prompted by financial crises, with a focus on their rationale, regulatory influences, and economic outcomes. It delves into the dual role of mergers—offering stability while posing potential risks, such as market concentration and systemic vulnerabilities. Case studies from past crises, including the 2008 Global Financial Crisis, illustrate how mergers have reshaped the financial landscape. Additionally, the paper compares the approaches of developed and emerging economies in handling mergers during crises, emphasizing the challenges of regulatory alignment and integration. The analysis reveals that while mergers can enhance efficiency and financial resilience, they require robust oversight to ensure long-term sustainability. The paper concludes with recommendations to strengthen regulatory frameworks, promote sustainable banking practices, and prepare for future crises by fostering resilient financial systems. These insights contribute to understanding how financial crises influence merger trends and offer guidance for policymakers and industry leaders navigating economic uncertainty.